CONFLICT MODELLING IN HIGHLY INTERACTIVE PROBLEM SOLVER - Bogunenko, Mykola; Pyvovarska, Кaterina (Proceedings of National Aviation University (archive), 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->Describes a new concept in planning and problem solving for air traffic controllers with the help of Highly Interactive Problem Solver. The modeling results of interactive method for conflict resolution with help of the program developed by the authors are introduced<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->